Bidirectional cross-linguistic influence in motion event conceptualisation in bilingual speakers of Spanish and English - Aveledo, Fraibet; Athanasopoulos, Panos (IRAL - International Review of Applied Linguistics in Language Teaching, 2023)
We investigated bidirectional cross-linguistic influence on motion event (ME) expressions in bilingual speakers of two typological different languages (Talmy’s typology), Spanish (as L1) and English (as L2). Specifically, we investigated whether bilingual speakers struggle to learn ME expressions in the L2, and whether this process affects ME uses in the L1. Potential effects of L2 proficiency and L2 AoA in both L1 and L2 was also studied. ME expressions elicited from 6-second video-clips were analysed for manner and path components at the level of the verb and of the clause. Results support the hypothesis of bidirectional cross-linguistic influence on motion event conceptualization. In bilinguals’ L2, we observed patterns of restructuring, convergence and L1 transfer. In bilinguals’ L1, we reported structural and conceptualization patterns that seem to emerge from the contact with the L2. Proficiency and AoA showed modulation in the use of manner verbs on both L2 and L1.
Keywords: L1 transfer; L2 learning; motion event; proficiency; reverse transfer